Pulmonary vascular distensibility with passive leg raise is comparable to exercise and predictive of clinical outcomes in pulmonary hypertension. (12th January 2022) - Kozitza, Callyn J.; Dharmavaram, Naga; Tao, Ran; Tabima, Diana M.; Chesler, Naomi C.; Raza, Farhan
Abstract: Pulmonary vascular distensibility ( α ) is a marker of the ability of the pulmonary vasculature to dilate in response to increases in cardiac output, which protects the right ventricle from excessive increases in afterload. α measured with exercise predicts clinical outcomes in pulmonary hypertension (PH) and heart failure. In this study, we aim to determine if α measured with a passive leg raise (PLR) maneuver is comparable to α with exercise. Invasive cardiopulmonary exercise testing (iCPET) was performed with hemodynamics recorded at three stages: rest, PLR and peak exercise. Four hemodynamic phenotypes were identified (2019 ECS guidelines): pulmonary arterial hypertension (PAH) ( n = 10), isolated post‐capillary (Ipc‐PH) ( n = 18), combined pre‐/post‐capillary PH (Cpc‐PH) ( n = 15), and Control (no significant PH at rest and exercise) ( n = 7). Measurements of mean pulmonary artery pressure, pulmonary artery wedge pressure, and cardiac output at each stage were used to calculate α. There was no statistical difference between α‐exercise and α‐PLR (0.87 ± 0.68 and 0.78 ± 0.47% per mmHg, respectively). The peak exercise‐ and PLR‐based calculations of α among the four hemodynamic groups were: Ipc‐PH = Ex: 0.94 ± 0.30, PLR: 1.00 ± 0.27% per mmHg; Cpc‐PH = Ex: 0.51 ± 0.15, PLR: 0.47 ± 0.18% per mmHg; PAH = Ex: 0.39 ± 0.23, PLR: 0.34 ± 0.18% per mmHg; and the Control group: Ex: 2.13 ± 0.91, PLR: 1.45 ± 0.49% per mmHg. Patients with α ≥ 0.7% per mmHg had reduced cardiovascular death and hospital admissions at 12‐month follow‐up. In conclusion, α‐PLR is feasible and may be equally predictive of clinical outcomes as α‐exercise in patients who are unable to exercise or in programs lacking iCPET facilities.